Homologous expression of a subcomplex of Pyrococcus furiosus hydrogenase that interacts with pyruvate ferredoxin oxidoreductase. - R Christopher Hopkins; Junsong Sun; Francis E Jenney; Sanjeev K Chandrayan; Patrick M McTernan; Michael W W Adams (PLoS ONE, 2011)
Hydrogen gas is an attractive alternative fuel as it is carbon neutral and has higher energy content per unit mass than fossil fuels. The biological enzyme responsible for utilizing molecular hydrogen is hydrogenase, a heteromeric metalloenzyme requiring a complex maturation process to assemble its O(2)-sensitive dinuclear-catalytic site containing nickel and iron atoms. To facilitate their utility in applied processes, it is essential that tools are available to engineer hydrogenases to tailor catalytic activity and electron carrier specificity, and decrease oxygen sensitivity using standard molecular biology techniques. As a model system we are using hydrogen-producing Pyrococcus furiosus, which grows optimally at 100°C. We have taken advantage of a recently developed genetic system that allows markerless chromosomal integrations via homologous recombination. We have combined a new gene marker system with a highly-expressed constitutive promoter to enable high-level homologous expression of an engineered form of the cytoplasmic NADP-dependent hydrogenase (SHI) of P. furiosus. In a step towards obtaining 'minimal' hydrogenases, we have successfully produced the heterodimeric form of SHI that contains only two of the four subunits found in the native heterotetrameric enzyme. The heterodimeric form is highly active (150 units mg(-1) in H(2) production using the artificial electron donor methyl viologen) and thermostable (t(1/2) ∼0.5 hour at 90°C). Moreover, the heterodimer does not use NADPH and instead can directly utilize reductant supplied by pyruvate ferredoxin oxidoreductase from P. furiosus. The SHI heterodimer and POR therefore represent a two-enzyme system that oxidizes pyruvate and produces H(2) in vitro without the need for an intermediate electron carrier.